FACTORS AFFECTING THE PERFORMANCE OF HAJJ FUND INVESTMENT IN MALAYSIA - Sayyidah Ummu Sayyidah; Prayogo P Harto; Ahmad Baehaqi Baehaqi; Edy Suprpato (Airlangga International Journal of Islamic Economics and Finance, 2020)
This study aims to analyze the effect of Investment Costs, Investment Size and Asset Allocation Policy on Investment Performance of Hajj Funds in Malaysia. The method used in this study is a quantitative method with Malaysia Hajj Financial Report Financial Data for 2008 - 2017 and data analysis techniques using non-parametric linear regression analysis with theil method. The results of this study indicate that all three factors together have a significant effect on the investment performance of Hajj funds. However, only Investment Costs are significant to the Investment Performance of the Hajj Fund. While the Investment Size and Asset Allocation Policy are not significant to the Investment Performance of the Hajj Fund in Malaysia.